ANAK DAN KEJAHATAN SEKSUAL - Nada, Rifka Khoirun (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2023)
This research is motivated by the increasing number of cases of sexual violence against minors. The pros and cons that accompany giving sex education to children, the notion that sex education is not appropriate to be taught to children and the absence of a sex education curriculum in schools causes sex education to children to be increasingly neglected. So that many children do not get proper and sufficient sex education. This study aims to introduce sex education as a preventive measure for sexual violence against elementary school-age children in the digital era. This type of research is a type of library research (Library Research) which is descriptive qualitative or literature study using content analysis techniques. The results of this study are sex education efforts in efforts to prevent sexual violence in elementary school children in the digital era, including: 1) Children are given an understanding of gender differences, 2) Children must be taught about sexuality according to their stage of development, 3) Teach a culture of shame in Children, 4) Teach religious values to children, 5) Accompany and interact with children when using devices and digital media, 6) discuss the good and bad behavior of the characters in digital devices and media, and 7) avoid programs that display elements of violence , fear, sexuality and use of inappropriate language.